2020
DOI: 10.1002/ajmg.a.61543
|View full text |Cite
|
Sign up to set email alerts
|

Martsolf syndrome with novel mutation in the TBC1D20 gene in a family from Iran

Abstract: Warburg Micro syndrome and Martsolf syndrome are phenotypically overlapping autosomal recessive conditions characterized by multiple organ abnormalities involving the ocular, nervous, and endocrine systems. Warburg Micro syndrome, the more severe of the two conditions, is caused by loss of function mutations in RAB3GAP1, RAB3GAP2, RAB18, and TBC1D20 genes, whereas Martsolf syndrome has been attributed to less damaging mutations in RAB3GAP1 and RAB3GAP2 genes. We report the clinical description and molecular ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 15 publications
0
8
0
1
Order By: Relevance
“…Alguns achados faciais menos frequentes observados nos indivíduos com LGC são também observados em diversas síndromes que promovem dismorfismos faciais, tais como linha frontal do cabelo baixa (Elefteriou, et al, 2004;Friguls, et al, 2008), também observada na síndrome de Rubinstein-Taybi (Eser, et al, 2017), síndrome de Cornélia de Lange (Parenti, et al, 2017) e síndrome de Martsolf (Hozhabri, et al, 2020). A presença de hirsutismos localizados é frequente em várias doenças sistêmicas hereditárias, dentre elas a síndrome de Berardinelli-Seip.…”
Section: Resultsunclassified
“…Alguns achados faciais menos frequentes observados nos indivíduos com LGC são também observados em diversas síndromes que promovem dismorfismos faciais, tais como linha frontal do cabelo baixa (Elefteriou, et al, 2004;Friguls, et al, 2008), também observada na síndrome de Rubinstein-Taybi (Eser, et al, 2017), síndrome de Cornélia de Lange (Parenti, et al, 2017) e síndrome de Martsolf (Hozhabri, et al, 2020). A presença de hirsutismos localizados é frequente em várias doenças sistêmicas hereditárias, dentre elas a síndrome de Berardinelli-Seip.…”
Section: Resultsunclassified
“…Overall, TBC1D20 mutations were described in five families with Micro syndrome. However, Hozhabri et al reported an Iranian family with Martsolf due to a TBC1D20 mutation providing another evidence of the genetic heterogeneity of the syndrome 14 …”
Section: Discussionmentioning
confidence: 99%
“…However, the involvement of epigenetic or environmental factors cannot be ruled out. In view of all molecularly defined families with Martsolf, four had mutations in RAB3GAP2 , 3,6,12 two had mutations in RAB3GAP1 , 3,13 and one family had a mutation in TBC1D20 14 . In addition, Gumus reported a family with overlapping features of the two syndromes due to a splice site mutation in RAB3GAP2 gene 11 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations